Justifying Roy Bhaskar’s “Alethic Truth” Through T. F. Torrance’s Theological Critical Realism - McGeorge-Hill, Andrew (Theology and science, 2024)
Critical Realism (CR) as presented by Roy Bhaskar and T. F. Torrance is explored with the view to justify Bhaskar’s notion of “alethic truth” by utilising Torrance’s CR. The implications of Bhaskar’s CR for theological science will be highlighted, as compared to positivism, showing that positivist philosophy undermines theology as a science, whilst CR affirms theology as a scientific discipline. Such affirmation legitimates the possibility for a theological CR to substantiate Bhaskar’s alethic truth theory. The article will display that Torrance’s theological CR complements Bhaskar’s CR by evidencing Bhaskar’s alethic truth theory.